Somatic point mutations occurring early in development: a monozygotic twin study. Issue 1 (11th October 2013) - Li, Rui; Montpetit, Alexandre; Rousseau, Marylène; Wu, Si Yu Margaret; Greenwood, Celia M T; Spector, Timothy D; Pollak, Michael; Polychronakos, Constantin; Richards, J Brent
Abstract : The identification of somatic driver mutations in cancer has enabled therapeutic advances by identifying drug targets critical to disease causation. However, such genomic discoveries in oncology have not translated into advances for non-cancerous disease since point mutations in a single cell would be unlikely to cause non-malignant disease. An exception to this would occur if the mutation happened early enough in development to be present in a large percentage of a tissue's cellular population. We sought to identify the existence of somatic mutations occurring early in human development by ascertaining base-pair mutations present in one of a pair of monozygotic twins, but absent from the other and assessing evidence for mosaicism. To do so, we genome-wide genotyped 66 apparently healthy monozygotic adult twins at 506 786 high-quality single nucleotide polymorphisms (SNPs) in white blood cells. Discrepant SNPs were verified by Sanger sequencing and a selected subset was tested for mosaicism by targeted high-depth next-generation sequencing (20 000-fold coverage) as a surrogate marker of timing of the mutation. Two de novo somatic mutations were unequivocally confirmed to be present in white blood cells, resulting in a frequency of 1.2×10 −7 mutations per nucleotide. There was little evidence of mosaicism on high-depth next-generation sequencing, suggesting that these mutations occurred early in embryonic development. These findings provide direct evidence that early somatic point mutations do occur and can lead to differences in genomes between otherwise identical twins, suggesting a considerable burden of somatic mutations among the trillions of mitoses that occur over the human lifespan. Keywords: somatic mutation; monozygotic twins; genome-wide genotyping; next-generation sequencing; genetic discordance